Resource Use Efficiency in Mulberry Cocoon Production in Tamil Nadu: an economic analysis - S. Lakshmanan (Journal of Agricultural Extension Management, 2025)
Mulberry sericulture is one among agro-based rural enterprises, which helps in transformation of socio-economic development in the rural areas. This sector promises creation of own family employment and providing handsome returns throughout the year for marginal and small landholdings. Micro-level studies (Lakshmanan et al., 1998 and 1999; Jayaram et al., 1998) reveal that mulberry sericulture generates viable employment opportunities for hired and owned family members and assures periodical returns throughout the year under irrigated conditions